Analysis of Service Quality at Wamena Airport, Jayawijaya Regency - Nobert; Hizkia Charles Matheus Sapioper; Agus Priyanto (Polit Journal Scientific Journal of Politics, 2024)
Wamena Airport, as an important gateway to the Highland Papua, has less than optimal service quality compared to the applicable service standards. This study aimed to describe and analyze the quality of the passenger terminal services at Wamena Airport, Jayawijaya Regency as well as identify supporting and hindering factors to the service quality at Wamena Airport. This was mixed methods research. The quantitative research data were obtained by distributing questionnaires to 382 Wamena Airport passengers. Meanwhile, the qualitative data were obtained by interviewing 12 informants who were the managers, passengers, and users of Wamena Airport as well as staffs of the airline. The quantitative data were processed using factor analysis, while the qualitative data were analyzed using an inductive approach. The results showed that the quality of the passenger terminal services at Wamena Airport was not yet optimal. There were several aspects which had poor service quality, requiring improvement. There were nine supporting and hindering factors to the quality of the passenger services at Wamena Airport. The supporting factorsare interactional quality (delivery), security, reliability of services, value added, and airport ground-handling services. The hindering factors to the service quality are convenience, leisure facilities, access and mobility, and airport environment.